Energy Consumption and Economic Growth – New Insights into the Cointegration Relationship - Ansgar Belke; Christian Dreger; Frauke de Haan (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
This paper examines the long-run relationship between energy consumption and real GDP, including energy prices, for 25 OECD countries from 1981 to 2007. The distinction between common factors and idiosyncratic components using principal component analysis allows to distinguish between developments on an international and a national level as drivers of the long-run relationship. Indeed, cointegration between the common components of the underlying variables indicates that international developments dominate the long-run relationship between energy consumption and real GDP. Furthermore, the results suggest that energy consumption is price-inelastic. Causality tests indicate the presence of a bi-directional causal relationship between energy consumption and economic growth. – – Dieses Papier untersucht unter Einbeziehung von Energiepreisen die langfristige Beziehung zwischen Energieverbrauch und realen BIP für 25 OECD Länder von 1981 bis 2007. Durch die Unterscheidung von gemeinsamen und idiosynkratischen Komponenten mit Hilfe einer Faktoranalyse kann zwischen Entwicklungen auf internationaler und nationaler Ebene als Treiber der Langfristbeziehung differenziert werden. In der Tat deutet Kointegration zwischen den gemeinsamen Faktoren der zugrundeliegenden Variablen darauf hin, dass internationale Entwicklungen die langfristige Beziehung zwischen Energieverbrauch und realem BIP dominieren. Des Weiteren suggerieren die ökonometrischen Ergebnisse, dass der Energieverbrauch relativ preisunelastisch ist. Kausalitätstests ergeben eine bidirektionale kausale Beziehung zwischen Energieverbrauch und Wirtschaftswachstum.
Keywords: C33; O13; Q43; 330; Energy consumption; panel unit roots; panel cointegration; vector errorcorrection models; Granger causality; Energiekonsum; Wirtschaftswachstum; Kointegration; Kausalanalyse; Energiepreis; Preiselastizität; Schätzung; OECD-Staaten